Higher effect of plant species diversity on productivity in natural than artificial ecosystems - Flombaum, Pedro; Sala, Osvaldo E (Proceedings of the National Academy of Sciences - PNAS, 2008)
Current and expected changes in biodiversity have motivated major experiments, which reported a positive relationship between plant species diversity and primary production. As a first step in addressing this relationship, these manipulative experiments controlled as many potential confounding covariables as possible and assembled artificial ecosystems for the purpose of the experiments. As a new step in this endeavor, we asked how plant species richness relates to productivity in a natural ecosystem. Here, we report on an experiment conducted in a natural ecosystem in the Patagonian steppe, in which we assessed the biodiversity effect on primary production. Using a plant species diversity gradient generated by removing species while maintaining constant biomass, we found that aboveground net primary production increased with the number of plant species. We also found that the biodiversity effect was larger in natural than in artificial ecosystems. This result supports previous findings and also suggests that the effect of biodiversity in natural ecosystems may be much larger than currently thought.